6th North American Caribou Workshop 1-4 March 1994, Prince George, British Columbia, Canada and George River Caribou Workshop, 27-29 January 1994, Labrador City, Labrador, Canada. - Rolf Egil Haugerud (ed. in chief); Kent Brown (iss. eds.) (Rangifer, 1996)
Proceedings of the Sixth North American Caribou Workshop (NACW) and the proceedings of the George River Caribou Workshop (GRCW). The Sixth NACW was attended by over 200 people. Papers from the GRCW (with asterix) are interspersed where appropriate with the papers from NACW).